Application of polypyrrole and polypyrrole/polyethylenimine for the removal of some heavy metal ions from aqueous solution / Samira Hosseini - Hosseini, Samira (2013)
Polypyrrole (Ppy) prepared by chemical oxidation using FeCl3 as the oxidant has exhibited 100% sorption capacity for the removal of heavy metal ions (Pb, Ni, Cu, Cd and Zn) from aqueous solutions. Batch adsorption results showed that solution pH had a major impact on metal adsorption. 100% heavy metal absorption was found at pH 7. At both acidic and alkaline solutions beyond pH 7, the adsorption capacity of Ppy was substantially lowered. The effects of other important parameters such as initial concentration of lead stock solution, contact time and the sorbent dosage on the uptake of metallic ions were also investigated to identify the optimum adsorption. The isothermal study of product indicated the applicability of Langmuir equation in present study which shows the formation of multilayer polymer. The FTIR and EDX results confirm the presence of heavy metals in polymer matrix after treatment. The prepared adsorbent showed a surface area of 5.047 m2 by BET analysis. The SEM micrographs of the polymer look similar for both before and after adsorption of heavy metals. The calibration plot shows a linear response with correlation coefficient of 0.9998. This method is simple, fast and precise and the complete removal of lead ions from the wastewater was recorded